Liver Toxicity Incited by Rifampicin & its Remedy by Aqueous Extract Preparation of Stem Bark of Barberry (Berberis Lycium Royale) in Male Mice Model (Medical Forum Monthly, 2020)
Objective: To investigate the liver toxicity produced by Rifampicin and its amelioration by using aqueous extract of stem-bark of Barberry (Berberis Lycium Royale) in male mice.Study Design: Randomized control trial study.Place and Duration of Study: This study was conducted at the animal abode of National Institute of Health (NIH), Islamabad in cooperation with Riphah Institute of Pharmaceutical Sciences (RIPS), Islamic International Medical College (IIMC) & Army Medical College (AMC) for 1 month from April 2014 to May 2014.Materials and Methods: This research study was conducted on 56 male mice. Animals indiscriminately allotted into 4 groups (n=14). Group I: Control group fed on rodent pellet food and tap water. Group II: Drug toxicity induced group put up on Rifampin 50mg/kg BW. Group III: Lower dose aqueous extract group given Rifampicin & (150mg/kg BW) aqueous extract of stem bark of Barberry. Group IV: High dose aqueous extract group kept on Rifampicin & (200mg/kg BW) of aqueous extract of Barberry via gavage tube orally. Baseline blood samples stockpiled at day 0 and serum values of Alanine aminotransferase (ALT) were recorded. Progress of experimental research was evaluated by serum measurement of Alanine aminotransferase (ALT) at day 15. At the end of experimental research on day 30 blood samples were collected by intra-cardiac puncture technique. Serum separated from blood samples were preserved in sterile containers at temperature of 4oC for analysis of serum Alanine aminotransferase (ALT). SPSS version 20 utilized for analysis of statistical data & p-value (<0.05) regarded as significant.Results: Serum Alanine aminotransferase (ALT) level (17-77 U/L) was recognized as normal range. Group I showed normal level of (56 U/L). Group II displayed extreme drug hepatotoxicity with very high value of (188.3 U/L). Serum value of ALT measured in Group C was (96.6 UL) & (56 UL) in Group D. Aqueous extract of stem-bark of Barberry restored serum Alanine aminotransferase (ALT) levels in group III (98.8 UL) & more remarkable improvement in Group IV with level of (58 UL).Conclusion: Aqueous extract of stem-bark of Barberry (Berberis Lycium Royale) proved amazing protective activity for rifampicin induced liver toxicity in high doses in comparison to less doses.